Kilka uwag na temat ideologii multikulturalizmu i jej skutków w dziedzinie polityki i prawa - Skrzydlewski, Paweł (Społeczeństwo, 2022)
By presenting the real outcome that occur in the field of law and politics, the author of the article makes an attempt to define and explain the phenomenon of multiculturalism and the ideology promoting that phenomenon. The considerations are of philosophical character. The Author claims that promotion of multiculturalism in social life leads to severe negative results and is in opposition to the rules and principles of Latin civilization that was created with the pedagogical activities of the Catholic Church. Following the instructions of F. Koneczny, the author justifies that the theoretical and practical aspects of multiculturalism usually constitute the phenomenon of unsuccessful attempts of civilizational synthesis. Although cultural pluralism established on the basis of one civilization has a positive impact of human development, civilizational pluralism is always the cause of painful and detrimental conflicts in personal, family, and political life. In this case, the assessment criterion is human nature and its ideality, comprehensive for human mind in philosophical cognition